The Effect of Vitamin D Supplementation on Autoimmune Bullous Skin Disorder Intensity Score on Bullous Pemphigoid and Acute Kidney Injury: A Case Report - Rahmita, Kartika Soka; Diyah Eka Andayani; Diana Sunardi (HM Publisher, 2024)
Introduction: Bullous pemphigoid is the most common bullous-type autoimmune disease. Hypovitaminosis D is often associated with autoimmune disease and found in 86,7% bullous pemphigoid patients. Vitamin D supplementation in bullous pemphigoid patients ought to ameliorate its clinical symptoms. Case presentation: A-58 years old male patient with bullous pemphigoid and acute kidney injury admitted with a chief complaint of infected blisters all over the body. The patient had been treated for 1 week with worsening swallowing pain and low intake. On the 12th day of hospitalization, the patient was given calcitriol supplementation of 0,25 mcg per day. There was an improvement in clinical symptoms shown on autoimmune bullous skin disorder intensity score (ABSIS) from 57 on inpatient day 7 to 17.5 on inpatient day 20. Patient discharged on the 20th day of hospitalization with no emerging blisters and the ability to swallow minced food by mouth. Conclusion: Calcitriol supplementation of 0,25 mcg per day for 10 days helps to improve the ABSIS score in bullous pemphigoid patient with acute kidney injury. Administration of calcitriol is considered safe and well tolerated.